AKSESIBILITAS PETANI DALAM AGRIBISNIS BAWANG MERAH DI LAHAN PASIR PANTAI KECAMATAN SANDEN KABUPATEN BANTUL - Witjaksono, Roso; Mudiyono, -; Hariadi, Sunarru Samsi (9-772301-994005, 2013)
The coastal land is the marginal land that  was managed as productive agricultural land. Since 1990 farmers have been using coastal land to cultivate the red onion. Agribusiness development of red onion in coastal land  need to be  supported by capital,  production and processing facilities and market. This  research aimed (1) to know the farmers accessibility toward capital, production and processing facilities and market, (2) the influence of the level of farmers accessibility toward level of adoption on agribusiness of red onion in coastal land.  Location of the research was in Sanden District of Bantul Regency. Srigading village was chosen purposively as sample because there were majority of farmers doing agribusiness of red onion, and then from this sample village was chosen purposively one sample of farmers group  which majority of members as agribusinessman of red onion, namely Manunggal farmers group.  From this farmers group sample were taken 60 respondents by census method. Data were analysed by using multiple linear regression and descriptive statistics. The research results showed that the level of  farmers accessibility was considerably high;  and the level of farmers accessibility was  significantly and positively influenced by the level of adoption on agribusiness innovation. Farmers attitude,  farmers motivation,  the role of farmers group, and the role of extension worker were not significantly influenced  by the level of adoption on agribusiness innovation